2004
DOI: 10.1542/peds.2004-0955
|View full text |Cite
|
Sign up to set email alerts
|

Hyperlactatemia in Human Immunodeficiency Virus–Uninfected Infants Who Are Exposed to Antiretrovirals

Abstract: ABSTRACT.Objective. Exposure to nucleoside analogues in fetal or early life has been associated with rare clinically significant mitochondrial toxic effects, mainly neurologic symptoms. Lactate (LA) measurements have been used to monitor nucleoside-related mitochondrial toxicity. Our aim was to determine the prevalence, clinical evolution, and risk factors for hyperlactatemia in our cohort of human immunodeficiency virus (HIV)-uninfected children who were exposed to antiretrovirals.Methods. We conducted a pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
13

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(55 citation statements)
references
References 36 publications
1
41
0
13
Order By: Relevance
“…The findings of this investigation are consistent with those of previous studies that found no association between in utero ARV exposure and neurologic outcomes, such as MD, [10][11][12][13]20,21 neurologic events, 14,21 and congenital abnormalities 15 among HEU infants. However, there are other studies that did find associations between in utero ARV exposure and MD, 4,8 hyperlactatemia, 22 febrile seizures, 6 and neurologic dysfunction. 7 Our analysis examined differences by specific ARV drug among all cART-exposed infants, while other studies compared cART-exposed infants to those unexposed.…”
Section: Discussionmentioning
confidence: 92%
“…The findings of this investigation are consistent with those of previous studies that found no association between in utero ARV exposure and neurologic outcomes, such as MD, [10][11][12][13]20,21 neurologic events, 14,21 and congenital abnormalities 15 among HEU infants. However, there are other studies that did find associations between in utero ARV exposure and MD, 4,8 hyperlactatemia, 22 febrile seizures, 6 and neurologic dysfunction. 7 Our analysis examined differences by specific ARV drug among all cART-exposed infants, while other studies compared cART-exposed infants to those unexposed.…”
Section: Discussionmentioning
confidence: 92%
“…2 A similar potential for mitochondrial toxicity from in utero exposure to ARV therapy has been suggested by primate studies, in which dose-related fetal abnormalities in mitochondrial structure and function have been reported in skeletal muscle, cardiac muscle, and brain. 3,4 Although transient hyperlactatemia is common in infants perinatally exposed to ARV therapy, 5,6 only rare cases of symptomatic hyperlactatemia have been reported. In these cases of lactic acidosis, the central nervous system was involved frequently and seems to be particularly vulnerable to mitochondrial insults.…”
mentioning
confidence: 99%
“…The inhibitory effect of ZDV on both HIV reverse transcriptase and DNA polymerase γ, an essential protein for mitochondrial DNA replication, is well known (2,3); the impact of the other NRTIs and other classes of ARV is less clear. Mitochondrial dysfunction due to ARV exposure before, during, or after birth is a broader toxicity that could have a continuing influence on childhood development; so, it is not surprising to find in our study a significant association between antenatal exposure to multiple NRTIs and developmental delay and/or behavioral disorders; however PACTG 219/219C found no overall association between ARV exposure in utero and neurologic development at 2 years of age in 1,037 HEU (9).…”
Section: Discussionmentioning
confidence: 99%
“…However, this benefit is counterbalanced with possible adverse drug effects related to in utero and neonatal exposure to antiretroviral (ARV) drugs: premature delivery, birth defects, short-term reversible biological abnormalities (anemia, neutropenia, hyperlactatemia) or persistent clinical and biological abnormalities (mitochondrial toxicity) (2)(3)(4). In high-income countries, guidelines recommend treating pregnant women with triple-combination ART and to increase the number of HIV infected women receiving therapy before conception; so fetuses are more and more exposed to ARV during gestation.…”
Section: Introductionmentioning
confidence: 99%